The Impact of Noise on Hearing in Intensive Care Unit Nurses - Abitağaoğlu, Süheyla; Öztaş, Alev; Şimşek Ceviz, Fatma; Köksal, Ceren; Aslan Dündar, Tuğba; Turan, Güldem; Erdoğan Arı, Dilek (Acta Medica, 2020)
Introduction: The noise levels in the ICUs exceed the levels suggested by the World Health Organization, because of the noises caused by devices and human noises. The aim of this study is to retrospectively examine the changes in audiometry results of nurses working in ICU. Methods: The audiometry results of nurses who worked for an uninterrupted period of 1 year in ICU in the last 3 years were examined retrospectively based on the results recorded at the time of employment and in the last year of working. Age, gender, years of work, assessments of hearing level and high frequency hearing losses were recorded. The normal level of hearing was accepted as 0-25dB. Results: Totally 10 male (25.6%), 29 female (74.4%) were included in the study. The mean age was 26.97 ± 4.69 years and the mean time of employment was 1.82 ± 0.91 years. The mean values of pure tone levels during the years of working were within the normal limits but a significant increase was observed. Two subjects (5.1 %) were confirmed to have high frequency hearing loss. Discussion and Conclusion: We believe that safety of the staff might be improved by reducing the level of noise in the ICUs and identifying the people at risk with yearly audiometry follow-ups.